Experimental Investigation Of The Flotation Stability Of A Helicopter After Ditching - Tödter, S.; Neugebauer, J.; Moctar, O. el; Harms, S.; Schellin, T.E. (My University, 2024)
Recent helicopter accident reviews show that more than 50% of all fatalities after ditching happened due to helicopter capsizing and, consequently, drowning of passengers and crew. In the present study, we experimentally investigated the flotation stability of a modern light helicopter equipped with a state-of-the-art flotation system. We monitored waves and sea spectra, measured helicopter motions and evaluated capsize probabilities for significant wave heights of 5 and 6 m. Resulting capsize probabilities were up to 13.1%. The helicopter was also tested with attached scoops, which did not show a positive effect on capsize probabilities and roll angles. Additionally, the effect of one opened cabin door was studied, which had no effect on the flotation stability.